Association Between Adolescents Perceived for Behaviour In Accessing Mental Health Services - Isni, Khoiriyah; Nisa, Khairan; Nurfatona, Winda Yulia; Santri, Ichtiarini Nurullita (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
The government of Indonesia provides programs to make it easier for adolescents to access mental health services. Adolescents are very vulnerable to mental and emotional health disorders, but there is low coverage of mental health services in primary health care. This study uses the theory of health belief models to examine how adolescents perceive having access to mental health services. This study used a cross-sectional design for 55 unmarried adolescents (15-24 years old) in Yogyakarta with a total sampling technique. Most adolescents (83.6%) perceive many barriers to accessing mental health services, so their self-efficacy becomes low (53.7%). Nevertheless, they have cues to act reasonably well (58.2%). Adolescents who perceive barriers (p-value = 0.007) and cues to action (p-value = 0.031) have a significant relationship with the behaviour of accessing mental health services. Meanwhile, perceived susceptibility (p-value = 0.909), perceived severity (p-value = 0.420), perceived benefits (p-value = 0.980), and self-efficacy (p-value = 1,000) did not have a significant relationship. The findings demonstrated that adolescents have sound cues to action in accessing mental health services, but low self-efficacy is thought to be the barrier.